The 2010 International Power Electronics Conference - ECCE ASIA - 2010
DOI: 10.1109/ipec.2010.5544591
|View full text |Cite
|
Sign up to set email alerts
|

New generation motor for energy saving

Abstract: Reduction of electrical consumption of a electric vehicle (EV) and electrical appliance is one of solutions for reduction of CO2 gas. Then, we have developed a novel permanent magnet motor for energy saving. In this paper, we propose a novel motor that can change magnetic flux by a new method magnetizing a permanent magnet and clarify the principle and unique characteristics. Furthermore, the results of analysis and experiments prove that the novel motor can change the flux of permanent magnet on load and has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 2 publications
1
15
0
1
Order By: Relevance
“…Therefore, the magnetizing current becomes the d-axis current in the new pole after pole changing. Also, the experimental results from a previous work [6], [7] have confirmed that the PM in the motor obtained using the magnetic analysis can be demagnetized and magnetized. Fig.…”
Section: Magnetization Characteristics Of the Motorsupporting
confidence: 64%
See 2 more Smart Citations
“…Therefore, the magnetizing current becomes the d-axis current in the new pole after pole changing. Also, the experimental results from a previous work [6], [7] have confirmed that the PM in the motor obtained using the magnetic analysis can be demagnetized and magnetized. Fig.…”
Section: Magnetization Characteristics Of the Motorsupporting
confidence: 64%
“…6 shows the magnetic properties of variable and constant magnetized magnets used in the model. The variable magnetized magnet that we have previously experimentally produced is a samarium cobalt (SmCo) magnet [7]. Therefore, it seems that the cost of the variable magnetized magnet may be same or less than that of a conventional SmCo magnet because the variable magnet has the potential to reduce the volume of the cobalt component.…”
Section: A Motor Model Used For Fem Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1. RS-PM motor specifications 6 show the magnetizations of the VMMs and CMMs, respectively, that are associated with changes from the PS-mode to the NS-mode. Here 1 pu is the rated current (current density = 4 A/mm 2 ), which shifts the phase of the current flow of the armature windings to magnetize the VMMs.…”
Section: Magnetization Characteristics Of the Reversible Salient Polementioning
confidence: 99%
“…Liu는 메모리 전동기에 자계 분석을 수행하였고 [4], 그리고 Sakai는 영구 자석의 감자 및 재자화에 의해 자속이 변화될 수 있는 가변 자기력 모터를 제안했다 [5]- [8]. Lee는 프라이자흐 모델링을 사용하여 극변환시 의 영구자석의 감자 전류 산정 및 특성 해석을 하였다 [9]- [10], Sakai는 실험 결과 및 분석에 의한 기초로 전동기 부하에 자속을 변화할 수 있음을 확인 했다 [5]- [6]. …”
unclassified